PROSEDUR PENERIMAAN TAMU INDIVIDUAL CHECK-IN OLEH PETUGAS PENERIMAAN TAMU DI HOTEL THE RITZ CARLTON NUSA DUA BALI - Ni Wayan Windya Fridajuniari; Ni Luh Putu Sri Widhiastuty; I Ketut Budiasa (Universitas Triatma Mulya, 2023)
The purpose of this study was to determine the procedure of reception officers in handling individual check-in guests and the obstacles faced by reception officers in handling individual check-ins so that it can be seen the efforts made by reception officers in handling individual check-in guests. This research uses data collection techniques in the form of interviews, observation, and documentation with qualitative descriptive data analysis techniques. What should be known is the procedure for the reception staff in handling individual check-in guests so that it can be seen the procedures for the reception staff in handling individual check-in guests by presenting the results of interviews, observations and documentation, it can be concluded that the procedures for reception officers are veryinfluential in handling individual check-in guests.